Design of Dual Frequency Microstrip Square patch antenna - Sohiful Anuar, Zainol Murad; W., Ismail (Kolej Universiti Kejuruteraan Utara Malaysia (KUKUM), 2009)
Organized by Kolej Universiti Kejuruteraan Utara Malaysia (KUKUM), 18th - 19th May 2005 at Putra Palace Hotel, Kangar.